Managing multi-cultural engineering teams in Egypt - Busada, Rania Joseph (AUC Knowledge Fountain, 2015)
The exercise of project management altered drastically over the past two decades and is currently driven by the growing demand of standardizing the industry’s practice and the emerging globalization of the industry. According to the literature review, one of the obstacles facing the development of the engineering teams in both developed and developing countries is the poor performances of multi-located and multi-cultural teams. The literature review reflects on the influences of the culture complexity and social diversity on the multi-cultural team’s performances. There have been a number of empirical studies that focus on the performances of the effectiveness of these teams. However most of the studies carried out focused on the individual’s experience within the context of developed countries. Given the global trend towards internationalization, there is a need to understand the parameters that determine the success of the foreign firms operating in the Egyptian construction market. This thesis is intended to explore the influences of the multi-national firms on the designers in the Egyptian construction industry and the various obstacles faced by the formal due to the diversity in their teams. The research employed a qualitative experiment on multi-cultural multi-located teams in one of the foreign firms in Egypt in order to capture the influences of the social and culture diversity on their performances. A quantitative survey was also conducted to gather relevant information about the multi-cultural teams from the Egyptian and foreign leaders in the construction industry. The verdict of the mixed method methodology illustrates the importance of considering the cultural index and various managerial techniques while operating in Egypt. The data gathered is analyzed using the Porter model, which was amended by various scholars to suit the needs of the designers in the construction industry. The data analyzed proposes a framework that includes key parameters to ensure superior performance by the multi-located and multi-cultural design engineering teams. The validation of the framework is conducted by follow-up deliberations with Egyptian and international experience managers from select companies participating in global engineering activities. The participants confirmed the significant of the proposed framework. A verification experiment is conducted on multi-cultural virtual teams, originally involved in the qualitative experiment, to ensure the significance of the framework developed in the real life situation. Following the framework’s establishment, a model is developed to assist the foreign companies’ rate their compatibility with the Egyptian construction industry. The aim of the model is to elevate the performances of the international company from a managerial perspective and provide recommendations in regard to the challenges faced while operating in Egypt. The model is validated through an external validity exercise. The thesis thus aimed at understanding the challenges, motives, benefits of the multi-cultural firms working in the Egyptian design construction industry. The framework and model developed are intended to provide a significant step to launch a successful operation of the multi-cultural and multi-located engineering teams in Egypt. The thesis concludes the importance of considering social and cultural aspects while developing a managerial approach which is to be formulated through an effective straightforward organizational culture. However with the continuous changes in the construction industry, it is highly recommended that future research and experiment be conducted on the multi-cultural teams in Egypt taking various socio-economic variations into consideration.